TACKLING THE NON-COMPLIANCE OF TAXPAYERS ON DIGITAL ECONOMY IN INDONESIA: A RATIONAL CHOICE LITERATURE: A Rational Choice Literature - Leo B. Barus; Yudha Pramana (Scientia Integritas Utama, 2022)
The increasingly widespread internet penetration shows that digital taxes can be one of the levers of state tax revenue. However, there are still potential challenges of tax non-compliance that must be considered by the Directorate General of Taxes (DGT) to handle them, which one is by using rational choice theory. It was concluded that in dealing with tax avoidance and tax evasion in the digital economy sector in Indonesia, the DGT needs to consider rational choice theory (by exploring contexts consisting of certainty, uncertainty, strategy, and group choice) in establishing and enforcing the law.